REGIONAL POLICY IN MANAGING OIL PALM WASTE AS RENEWABLE ENERGY IN SOUTH KALIMANTAN PROVINCE - Ifrani Ifrani; Muhammad Topan; Nurmaya Safitri; Tiya Erniyati (Scholar Center, 2021)
Besides producing CPO and KPO, oil palm also produces a lot of waste. Oil palm waste can be managed and utilized. This study aims to determine how oil palm waste is managed, the authority of local governments to regulate oil palm waste management in South Kalimantan Province. Third, what is the concept of future local government policies in utilizing oil palm waste as a new and renewable energy development in South Kalimantan? The research method used is normative juridical research, the research that is focused on examining the application of the rules or norms in positive law, analyzing in-depth and holistically, from all aspects comprehensively, sourced from library research using legal materials, namely primary legal materials, secondary legal materials, and tertiary legal materials, to answer regulatory issues in the legislation regarding the Policy on the Use of Oil palm Waste as New and Renewable Energy in South Kalimantan Province. The result shows that Indonesia has been able to create renewable energy from the oil palm industry. However, the government needs to regulate the use of oil palm shell waste through local regulations and policies. With the participation of policymakers, and focus for development. It can creates jobs, increase and develop disadvantaged areas and in the end will reduce the level of poverty.